(untitled) (International Journal of Engineering and Computer Science, 2013)
Recently the cloud computing has been gaining significant importance in almost all the fields. In this survey we discuss the limitations and opportunities of deploying data management issues on cloud computing platforms. A cloud database management system is a distributed database that delivers computing as a service. The various issues related to security that has to be offered by the Database as a service is studied. Various operations such as Scaling, provisioning, performance tuning, privacy and backup. This study also reveals about consistency rationing and various adaptive policies.